Metal oxide patterns of one-dimensional nanofibers: on-demand, direct-write fabrication, and application as a novel platform for gas detection. Issue 43 (15th October 2019) - Lim, Kyeorei; Jo, Young-Moo; Yoon, Ji-Wook; Lee, Jong-Heun
Abstract : On-demand, direct-write fabrication of metal oxide patterns composed of one-dimensional nanofibers using near-field electrospinning is demonstrated and their formation mechanism as well as potential applications are investigated. Abstract : To organize one-dimensional (1D) metal oxides into highly ordered and controllable architectures on the required regions remains challenging. Herein, we report for the first time the facile, versatile, and on-demand fabrication of metal oxide patterns comprising 1D nanofibers via near-field electrospinning (NFES), which have a wide variety of potential applications in sensors, optoelectronic circuits, and functional nanoelectronics. Grids, diamonds, and hexagrams of In2 O3, Co3 O4, and NiO nanofibers are first demonstrated, and the underlying mechanisms for fiber formation are systematically investigated with respect to the experimental parameters of NFES. Furthermore, we propose the nano-architectures as a novel gas sensing platform that exhibits an unprecedentedly high gas response (resistance ratio, S T = 239, T: trimethylamine) and selectivity ( S T S E −1 > 7, E: ethanol) to 5 ppm trimethylamine compared with thin film counterparts ( S T = 24, S T S E −1 ≈ 1). The research provides a vital breakthrough to fabricate metal oxide nano-architectures of 1D nanofibers and new platforms to design next-generation functional nanodevices for a wide range of emerging applications.